Solid-Phase Synthesis of Oligonucleotide Conjugates Useful for Delivery and Targeting of Potential Nucleic Acid Therapeutics - Lnnberg, Harri (Bioconjugate chemistry, 2009)
Olignucleotide-based drugs show promise as a novel form of chemotherapy. Among the hurdles that have to be overcome on the way of applicable nucleic acid therapeutics, inefficient cellular uptake and subsequent release from endosomes to cytoplasm appear to be the most severe ones. Covalent conjugation of oligonucleotides to molecules that expectedly facilitate the internalization, targets the conjugate to a specific cell-type or improves the parmacokinetics offers a possible way to combat against these shortcomings. Since workable chemistry is a prerequisite for biological studies, development of efficient and reproducible methods for preparation of various types of oligonucleotide conjugates has become a subject of considerable importance. The present review summarizes the advances made in the solid-supported synthesis of oligonucleotide conjugates aimed at facilitating the delivery and targeting of nucleic acid drugs.